The Art of Successful Information Systems Outsourcing - Gefen, David (Business Expert Press, 2010)
Ebook from IG Library ; As with other pressing issues of information systems (IS) management, managing IS outsourcing also began as a solution to industry needs, and much of this book is accordingly based on industry experience cloaked as it were in academic theory garb to add depth to these proven practices as well as allow for borrowing insight from other academic disciplines.